Derivative Spectrophotometry and PAM-Fluorescence in Comparative Biochemistry - Saakov, Vladimir S.; Krivchenko, Alexander I.; Rozengart, Eugene V.; Danilova, Irina G. (Springer International Publishing : Imprint: Springer, 2015)
This book presents various examples of how advanced fluorescence and spectroscopic analytical methods can be used in combination with computer data processing to address different biochemical questions. The main focus is on evolutionary biochemistry and the description of biochemical and metabolic issues; specifically, the use of pulse amplitude modulated fluorescence (PAM) for the functional analysis of the cellular state, as well as results obtained by means of the derivative spectroscopy method characterizing structural reorganization of a cell under the influence of external factors, are discussed. The topics presented here will be of interest to biologists, geneticists, biophysicists and biochemists, as well as experts in analytical chemistry, pharmaceutical chemistry and radiochemistry and radioactivation studies with protonen and alpha-particles. It also offers a valuable resource for advanced undergraduate and graduate students in biological, physical and chemical disciplines whose work involves derivative spectrophotometry and PAM-fluorescence.